Niches and Sculptures of the Imaginary Realm—Revisiting the Fowan Rock Carvings, Beishan, Dazu - Sun, Bo (Religions, 2024)
The Fowan Cliff Carvings are a key part of the Dazu Grottoes. Formed in a southern and northern stretch, the 290 individual niches at Fowan were mostly sculpted from the Late Tang to the Southern Song. Previous research by archaeologists and art historians has used typological and iconographic methods to periodize these niches and debate the themes behind particular niche sculptures. This essay employs niche inscriptions in a discussion of typical Fowan niche contents, matching lay feasting activities onto the period background behind their construction. These individual case studies grant an understanding of the overall atmosphere at Fowan through the shared inclinations or connections between niches, also reflecting specific niche sculptures via holistic analysis. This method, repeatedly examining the relationship between the niches and site from the perspective of “venue”, helps us restore a sense of situatedness when facing different eras of Fowan and to understand the choice in statue content, changes in niche content, and the design underlying niche form.